Providing timely quality care after-hours: Perceptions of a hospital model of care. Issue 1 (February 2019) - Fossum, Mariann; Hewitt, Nicky; Weir-Phyland, Janet; Keogh, Martin; Stuart, Joshua; Fallon, Kethly; Bucknall, Tracey
Abstract: Background: Nurses working night shift are key-players in the acute care team, however, their work environment has been characterised by suboptimal leadership, communication inadequacies, limited resources, and a lack of adequate support. Aim: The aim of this study was to investigate nurses' perceptions of the Hospital at Night Team, a nursing model of care implemented to provide timely quality nursing care after-hours. Methods: The study used a descriptive design. Five focus groups were conducted, with a total of 34 nurses from 14 wards across a 600+ bed tertiary referral teaching hospital in Melbourne, Australia, one year after the Hospital at Night Team implementation. Focus group interviews were transcribed and subjected to thematic analysis. Findings: Themes arising were: changing role perceptions as the Hospital at Night Team was embedded into the organisation; the impact of technology on workflow and responsiveness; refinement of services occurring over time with feedback and evaluation; and facilitating collaboration and learning across disciplines. Discussion: The Hospital at Night Team role evolved to offer more support for specialised procedures as well as a large amount of direct care. The services were perceived to have been refined over time, responding to feedback and evaluation of the service. Conclusions: The Hospital at Night Team nursing model of care provides flexibility, support, collaboration and shared learning across wards. Further research should investigate the effect of the Hospital at Night Team nursing model of care on patient outcomes.